High-toughness aluminum-based composite material with physical bonding interface as well as preparation method and application of high-toughness aluminum-based composite material

Through high-energy ball milling and low-temperature hot extrusion processes, high-strength aluminum-based composite materials with physical bonding interfaces were prepared, which solved the interfacial reaction and interface diffusion of NiTi/Al composite materials, significantly improved the tensile strength and elongation, and was suitable for Aerospace and automotive engineering.

CN119220842AActive Publication Date: 2024-12-31HARBIN INST OF TECH

Patent Information

Application Number
CN202411338842.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Existing NiTi/Al composites have problems with interface reaction and interface diffusion, resulting in reduced interface binding strength and changes in NiTi components. The spherical shape of NiTip leads to a small interface binding area and poor deformability, resulting in matrix-enhanced phase particle interface. Failure prematurely during loading.

Method used

Mix SiCnp with small-sized aluminum matrix powder by high-energy ball mill, and mix NiTip with large-sized aluminum matrix powder to form Al-SiCnp-NiTip composite powder. The preparation of physical bonds is prepared by low-temperature discharge plasma sintering and low-temperature hot extrusion processes. The interface of high-strength aluminum-based composite material ensures no interface reaction and improves the interface combination between NiTip and Al matrix.

Benefits of technology

It significantly improves the tensile strength and elongation of composite materials, with tensile strength reaching ≥285GPa and elongation of ≥13.5%, and has application potential in the fields of aerospace and automotive engineering, solving the loading process of traditional NiTi/Al composite materials interfaces premature failure problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220842A_ABST
    Figure CN119220842A_ABST
Patent Text Reader

Abstract

The invention discloses a high-toughness aluminum-based composite material with a physical bonding interface and a preparation method and application of the high-toughness aluminum-based composite material. The invention belongs to the field of aluminum-based composite materials. The invention aims to solve the technical problem of premature failure of a matrix-reinforced phase particle interface in the loading process of the existing NiTip reinforced aluminum-based composite material. The method comprises the following steps: firstly, mixing SiCnp and small-size aluminum-based matrix powder through high-energy ball milling; then NiTip and large-size aluminum-based matrix powder are subjected to high-energy ball milling and mixing; then the two kinds of mixed powder and non-ball-milled aluminum powder are subjected to low-speed ball milling and mixing, and Al-SiCnp-NiTip composite powder is obtained; and finally, carrying out low-temperature discharge plasma sintering and low-temperature hot extrusion. The method disclosed by the invention can also be used for preparing other metals and alloy composite materials thereof. The obtained composite material has high strength and toughness, and is applied to the fields of aerospace and automotive engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aluminum-based composite materials, and in particular relates to a high-strength and tough aluminum-based composite material with a physical bonding interface, and a preparation method and application thereof. Background Art

[0002] NiTi (SMAs) undergoes a martensitic phase transformation when subjected to external stimuli. The shape memory effect or superelastic deformation of SMAs is utilized to cause them to deform during the process of being subjected to external forces, thereby playing the role of energy dissipation and phase transformation toughening. Previous studies have shown that the mechanical properties of Al, Mg and Ag composites reinforced with NiTi alloys are greatly improved. The unique shape memory effect (SME) or superelastic deformation of NiTi alloys has been used to apply compressive stress to the matrix, thereby enhancing the ductility and fatigue resistance of the composites.

[0003] However, the current NiTi / Al composites have the following problems: (1) NiTips are prone to serious interface reactions and interface diffusion with the matrix alloy, leading to the formation of intermetallic compounds, which not only damages the interface bonding strength, but also causes changes in the NiTi composition and reduces the SME capacity. (2) Most NiTips in NiTip / Al composites are spherical, with a small interface bonding area with the Al matrix and poor deformability. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problem of premature failure of the matrix-reinforcement phase particle interface in the existing NiTip-reinforced aluminum-based composite materials during loading, and to provide a high-strength and tough aluminum-based composite material with a physical bonding interface and a preparation method and application thereof.

[0005] The technical solution of the present invention is as follows:

[0006] One of the purposes of the present invention is to provide a method for preparing a high-strength and tough aluminum-based composite material with a physical bonding interface, the method being carried out according to the following steps:

[0007] S1: mixing SiCnp with small-sized aluminum-based matrix powder by high-energy ball milling to obtain Al-SiCnp mixed powder;

[0008] S2: mixing NiTip with large-size aluminum-based matrix powder by high-energy ball milling to obtain Al-NiTip mixed powder;

[0009] S3: mixing the Al-SiCnp mixed powder, the Al-NiTip mixed powder and the unmilled aluminum powder by low-speed ball milling to obtain an Al-SiCnp-NiTip composite powder;

[0010] S4: The Al-SiCnp-NiTip composite powder is first subjected to low-temperature spark plasma sintering and then subjected to low-temperature hot extrusion to obtain a high-strength and tough aluminum-based composite material with a physical bonding interface.

[0011] It is further defined that the amount of SiCnp added in S1 is 1.1 to 7.5 wt. % of the small-sized aluminum-based matrix powder.

[0012] It is further defined that the small and medium-sized aluminum-based matrix powders in S1 include aluminum powder and its alloy powder, with a size of 5 to 15 μm.

[0013] It is further defined that the high energy ball milling speed in S1 is 300-400 rpm and the time is 8-15 h.

[0014] It is further defined that the amount of NiTip added in S2 is 11 to 50 wt.% of the large-sized aluminum-based matrix powder.

[0015] It is further defined that the large-sized aluminum-based matrix powder in S2 includes aluminum powder and its alloy powder, with a size of 50 to 150 μm.

[0016] It is further defined that the high energy ball milling speed in S2 is 300-400 rpm and the time is 8-15 h.

[0017] It is further defined that the mass ratio of the Al-SiCnp mixed powder, the Al-NiTip mixed powder and the unmilled aluminum powder in S3 is 1:1:(0.5-0.8).

[0018] It is further defined that the speed of the medium-low speed ball mill in S3 is 100-200 rpm and the time is 1-5 h.

[0019] It is further defined that the temperature of the low-temperature discharge plasma sintering in S4 is 500-530° C., the pressure is 40-60 MPa, and the time is 5-15 min.

[0020] It is further defined that the hot extrusion temperature in S4 is 400-430°C, the extrusion ratio is (16-25):1, and the extrusion rate is 0.1-0.5 mm / s.

[0021] The second object of the present invention is to provide a high-strength and tough aluminum-based composite material prepared by the above method, wherein the composite material has a tensile strength of ≥285GPa and an elongation of ≥13.5%.

[0022] The third object of the present invention is to provide a high-strength and tough aluminum-based composite material prepared by the above method for use in the fields of aerospace and automotive engineering.

[0023] A fourth object of the present invention is to provide an application of the above method in the preparation of high-strength and high-toughness metal-based composite materials.

[0024] It is further defined that the metal matrix is ​​one of Mg, Fe, Ti, Cu and their respective alloys.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] (1) The present invention adopts a low-temperature SPS + hot extrusion process to prepare a NiTi / Al composite material with no interface reaction and good interface bonding. Sintering is performed at a relatively low temperature to ensure no interface reaction, but the density is relatively low; combined with low-temperature hot extrusion, the densification of the composite material and good interface bonding (effective load transfer effect) are achieved.

[0027] (2) The present invention adopts high-energy ball milling to ball mill the circular NiTip and Al powder. Under higher ball milling energy, the NiTip is deformed from a spherical shape to an elliptical or flat strip shape, and the interface bonding between the NiTip and the Al matrix is ​​improved by increasing the surface area of ​​contact between the NiTip and the Al matrix. Then, low-temperature hot extrusion is selected to further promote the deformation of the NiTip by utilizing its large plastic rheological stress. This preparation method solves the problem of premature failure of the matrix-reinforcement phase particle interface of the traditional NiTi / Al composite material during loading. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The SEM image of the NiTi / Al composite material without interface reaction prepared in Example 1;

[0029] Figure 2 The SEM image of the NiTi / Al composite material with interface reaction prepared in Comparative Example 1;

[0030] Figure 3 The STEM image of the NiTi / Al composite material without interface reaction prepared in Example 1;

[0031] Figure 4 HAADF diagram of the NiTi / Al composite material without interface reaction prepared in Example 1;

[0032] Figure 5 The EDS image of the NiTi / Al composite material without interface reaction prepared in Example 1;

[0033] Figure 6 Graph showing room temperature tensile stress-strain curves of the NiTi / Al composite materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0036] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0037] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0038] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0039] Example 1: The preparation method of the high-strength and tough aluminum-based composite material with a physical bonding interface in this example is carried out according to the following steps:

[0040] S1: 0.28 g of SiCnp (average diameter ~43 nm) and 23.72 g of spherical aluminum powder (purity 99.9%, average diameter ~7.8 μm) were added to a planetary ball mill and mixed at 300 rpm for 10 h with a ball-to-material ratio of 15:1 to obtain Al-SiCnp mixed powder;

[0041] S2: 12.48 g of NiTip (Ni:Ti atomic ratio = 50.82:49.18, average diameter ~18.10 μm) and 47.52 g of spherical aluminum powder (purity 99.9%, average diameter ~72.48 μm) were added to a planetary ball mill, and mixed by high-energy ball milling at 300 rpm for 10 h, with a ball-to-material ratio of 15:1 to obtain Al-NiTip mixed powder;

[0042] S3: 24 g of Al-SiCnp mixed powder, 24 g of Al-SiCnp mixed powder and 12 g of unmilled aluminum powder (purity 99.9%, average diameter 72.48 μm) were added into a planetary ball mill, and mixed by high-energy ball milling at 200 rpm for 5 h, with a ball-to-material ratio of 15:1, to obtain Al-SiCnp-NiTip composite powder;

[0043] S4: Encapsulate the Al-SiCnp-NiTip composite powder in a graphite mold, then place the entire mold into a spark plasma sintering furnace and evacuate it to avoid powder oxidation contamination caused by contact with air, and perform spark plasma sintering. The selected sintering temperature is 530°C, the uniaxial pressure is 50MPa, and the selected holding time is 10min. After the sintering is completed, the furnace is cooled and the mold is placed in a ring furnace. From top to bottom, the mold contains an extrusion cup, a pure aluminum block, a sintered composite material and a graphite gasket. Low-temperature hot extrusion is performed. The selected hot extrusion temperature is 430°C, the holding time is 1.5h, and the extrusion ratio is 25:1; the extrusion rate is 0.5mm / s, and a high-strength and tough aluminum-based composite material with a physical bonding interface is obtained.

[0044] Comparative Example 1: The preparation method of the aluminum-based composite material for the interface reaction of this embodiment is carried out according to the following steps:

[0045] S1: 0.28 g of SiCnp (average diameter ~43 nm) and 23.72 g of spherical aluminum powder (purity 99.9%, average diameter ~7.8 μm) were added to a planetary ball mill and mixed at 300 rpm for 10 h with a ball-to-material ratio of 15:1 to obtain Al-SiCnp mixed powder;

[0046] S2: 12.48 g of NiTip (Ni:Ti atomic ratio = 50.82:49.18, average diameter ~18.10 μm) and 47.52 g of spherical aluminum powder (purity 99.9%, average diameter ~72.48 μm) were added to a planetary ball mill, and mixed by high-energy ball milling at 300 rpm for 10 h, with a ball-to-material ratio of 15:1 to obtain Al-NiTip mixed powder;

[0047] S3: 24 g of Al-SiCnp mixed powder, 24 g of Al-SiCnp mixed powder and 12 g of unmilled aluminum powder (purity 99.9%, average diameter 72.48 μm) were added into a planetary ball mill, and mixed by high-energy ball milling at 200 rpm for 5 h, with a ball-to-material ratio of 15:1, to obtain Al-SiCnp-NiTip composite powder;

[0048] S4: Encapsulate the Al-SiCnp-NiTip composite powder in a graphite mold, then place the entire mold into a spark plasma sintering furnace and evacuate it to avoid powder oxidation contamination caused by contact with air, and perform spark plasma sintering. The selected sintering temperature is 530°C, the uniaxial pressure is 50MPa, and the selected holding time is 10min. After the sintering is completed, the furnace is cooled and the mold is placed in a ring furnace. From top to bottom, the mold contains an extrusion cup, a pure aluminum block, a sintered composite material and a graphite gasket. Hot extrusion is performed. The selected hot extrusion temperature is 480°C, the holding time is 1.5h, and the extrusion ratio is 25:1. The extrusion rate is 0.5mm / s to obtain an aluminum-based composite material with an interface reaction.

[0049] Figure 1 This is the SEM of the composite material without interfacial reaction prepared in Example 1. Figure 1 It can be seen that after hot extrusion deformation, the Al-SiCnps zone is significantly elongated along the extrusion direction, the reinforcement phase is evenly dispersed, and the Al-NiTip and Al zone are mixed between the Al-SiCnp zones. The NiTip in the Al-NiTip zone is evenly distributed and the deformation of the NiTip is large, all developing into long strips, but in the case of large deformation, no obvious defects or interface reactions are found at the interface with the Al matrix, and it has good interface bonding.

[0050] Figure 2 The SEM of the composite material with interface reaction prepared in Comparative Example 1 is shown in FIG. Figure 2 It can be seen that when hot extrusion is performed at a higher temperature, the NiTip in the Al-NiTip zone is evenly distributed and the deformation of the NiTip is large, but the NiTip undergoes a serious interface reaction and obvious defects can be observed at the interface.

[0051] Figure 3 This is a STEM image of the composite material without interfacial reaction prepared in Example 1. Figure 3 It can be observed that NiTi is composed of fine nanoparticles, and the grains in the Al matrix are long strips after extrusion, with good interface bonding and no obvious defects; there are no obvious reaction products at the interface.

[0052] Figure 4 The HAADF diagram of the composite material without interface reaction prepared in Example 1 is shown in FIG. Figure 4It can be seen that the interface between NiTip and Al is straight, but there is a transition layer of ~10nm thickness.

[0053] Figure 5 The EDS image of the composite material without interface reaction prepared in Example 1 further confirms that the NiTi / Al interface is composed of an amorphous oxide interface layer of 5-15 nm thick, which is conducive to the combination of NiTip and aluminum matrix. In addition, there is no obvious inter-element diffusion between NiTip and Al matrix, the interface is very clear, and the NiTi / Al composite material without interface reaction is successfully prepared.

[0054] By performing room temperature tensile tests on the NiTi / Al composite materials prepared in Example 1 and Comparative Example 1, it was found that ( Figure 6 ),from Figure 6 It can be seen that the interface reaction has a great influence on the mechanical properties of NiTi / Al composites. Compared with NiTi / Al composites with interface reaction, the yield strength, tensile strength and elongation of NiTi / Al composites without interface reaction are significantly improved. The yield strength increased from 143.2MPa to 250.5MPa, an increase of 74.9%; the tensile strength increased from 192.0MPa to 285.7MPa, an increase of 48.8%; the elongation increased from 5.2% to 13.5%, an increase of 153.8%. It is worth noting that the existence of interface reaction has a direct impact on the strengthening effect of composite materials. This shows that the preparation of NiTi / Al composites without interface reaction has great potential in achieving the goal of strengthening and toughening aluminum-based composites.

[0055] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a high-strength and tough aluminum-based composite material with a physical bonding interface, characterized in that: The method: S1: mixing SiCnp with small-sized aluminum-based matrix powder by high-energy ball milling to obtain Al-SiCnp mixed powder; S2: mixing NiTip with large-size aluminum-based matrix powder by high-energy ball milling to obtain Al-NiTip mixed powder; S3: mixing the Al-SiCnp mixed powder, the Al-NiTip mixed powder and the unmilled aluminum powder by low-speed ball milling to obtain an Al-SiCnp-NiTip composite powder; S4: The Al-SiCnp-NiTip composite powder is first subjected to low-temperature spark plasma sintering and then subjected to low-temperature hot extrusion to obtain a high-strength and tough aluminum-based composite material with a physical bonding interface.

2. The method according to claim 1, characterized in that The amount of SiCnp added in S1 is 1.1-7.5wt.% of the matrix powder. The aluminum-based matrix powder includes aluminum powder and its alloy powder, with a size of 5-15μm. The ball milling speed is 300-400rpm and the time is 8-15h.

3. The method according to claim 1, characterized in that The amount of NiTip added in S2 is 11-50wt.% of the base powder. The aluminum-based base powder includes aluminum powder and its alloy powder, with a size of 50-150μm. The ball milling speed is 300-400rpm and the time is 8-15h.

4. The method according to claim 1, characterized in that: The mass ratio of Al-SiCnp mixed powder, Al-NiTip mixed powder and unmilled aluminum powder in S3 is 1:1:(0.5-0.8), the ball milling speed is 100-200 rpm, and the time is 1-5 h.

5. The method according to claim 1, characterized in that The sintering temperature in S4 is 500-530°C, the pressure is 40-60MPa, and the time is 5-15min.

6. The method according to claim 1, characterized in that In S4, the hot extrusion temperature is 400-430°C, the extrusion ratio is (16-25):1, and the extrusion rate is 0.1-0.5 mm / s.

7. The high-strength and tough aluminum-based composite material prepared by the method according to any one of claims 1 to 6, characterized in that: The composite material has a tensile strength of ≥285 GPa and an elongation of ≥13.5%.

8. Application of the high-strength and toughness aluminum-based composite material according to claim 7 in the fields of aerospace and automotive engineering.

9. Use of the method according to any one of claims 1 to 6 in preparing high-strength and high-toughness metal-based composite materials.

10. The use according to claim 9, characterized in that: The metal matrix is ​​one of Mg, Fe, Ti, Cu and their alloys.

Citation Information

Patent Citations

  • Method for preparing NiTi-fiber-enhanced 2219Al composite

    CN105313426A

  • Preparation method of interface-product-free SiC-CNTs double-phase reinforced aluminum-based composite material

    CN117568643A

  • Preparation method for enhancing toughness of aluminum-based composite material

    CN118241063A

  • Preparation method of heat-resistant aluminum-based composite material for piston

    CN118272706A

  • Preparation method of NiTi / Al composite material with improved elastic modulus

    CN118441168A

Cited By

  • SiCp reinforced aluminum matrix composite interface phase regulation and control method

    CN122503727A